Molecular Analysis and Morphological Characterization of Tor sp. using DNA Barcode COI from Telaga Rambut Monte, Blitar, East Java, Indonesia - Damayanti, Ayu Elysia; Rabbani, Calista Naya; Sulung, Cahya Ajeng Valenta Tresna; Rusdianto, Rusdianto; Nugroho, Endik Deni; Mamat, Noorhidayah Binti; Rahayu, Dwi Anggorowati (Biotropika: Journal of Tropical Biology, 2025)
The genus Tor (Cyprinidae) comprises highly diverse freshwater fishes widely distributed in Southeast Asia, including Indonesia. However, information on Tor species in several regions remains limited. This study aimed to identify Tor species from Telaga Rambut Monte, Blitar, using morphological analysis and molecular approaches based on COI DNA barcoding. Fish were collected through purposive sampling at depths of 1–2 m, and fin tissues were preserved in ethanol for DNA extraction. PCR amplification employed LCO1490 and HCO2198 primers, with sequence analysis conducted using BLAST and the BOLD System. Phylogenetic reconstruction applied Neighbour-Joining and Maximum Likelihood methods under the Kimura 2-Parameter model, supported by p-distance analysis with MEGA, Clustal X, BioEdit, and ABGD. Morphological characterisation confirmed the specimens as Tor tambra. COI gene amplification produced a 477 bp sequence, which showed 92% genetic similarity to the reference T. tambra. The phylogenetic tree revealed a distinct clade with a high bootstrap value (96%), clearly separating T. tambra from other congeners. Integrating morphological and molecular data provides robust evidence confirming the presence of T. tambra in Telaga Rambut Monte. This research represents the first study combining genetic identification, morphological analysis, and phylogenetic reconstruction of T. tambra from this locality. The findings contribute to understanding freshwater fish biodiversity in Indonesia and provide important baseline information on the distribution of local fish resources.